Between a Burden and Green Technology: Rishi Sunak’s Framing of Climate Change Discourse on Facebook and X (Twitter) - Kapranov, Oleksandr (Information & Media, 2024)
The issue of climate change has been one of the critical foci of political discourse worldwide (Wagner, 2023). Given that political debates and political discourse are quite often communicated on Social Networking Sites (SNSs), for instance, Facebook and X (Araújo & Prior, 2021), it appears highly relevant to tap into political actors’ discourse on SNSs that addresses the issue of climate change. Guided by the importance of SNSs in political discourse on climate change, the present article introduces and discusses a study on how Rishi Sunak, the current prime minister of the United Kingdom (the UK), frames the issue of climate change on his official Facebook and X accounts. Specifically, the aim of the study was to identify the types of frames used in Sunak’s climate change discourse in a corpus of his posts on Facebook and X. The corpus was collected and analysed in accordance with the methodology proposed and developed by Entman (2007). The results of the analysis revealed that Sunak’s framing of climate change involved a pragmatic economy-oriented aspect, which was presented discursively by imparting it a personalised dimension that involved multimodality. In particular, it was discovered that Sunak frequently framed the issue of climate change via the frames Burden and Green Technology. The findings were discussed in conjunction with the prior research on framing in climate change discourse.
Keywords: climate change; British political discourse; Facebook; frame; framing; X (Twitter)